PELAYANAN PENGURUSAN AKTA PERKAWINAN DIKANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Raja Surya Darma; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study dilator background by a phenomenon found in time do prasurvay field, which appear to have good maintenance service of a marriage certificate At the Office of Population and Civil Registration Pekanbaru. With the aim to identify and explain the maintenance of a marriage certificate services when At the Office of Population and Civil Registration Pekanbaru and what are the constraints. In line with the purpose of the study, the population in this study is the staff of Department of Population and Civil Registration section of Pekanbaru on marriage and society. Where sampling techniques to employees using census techniques and communities with incidental sampling technique. Types of data collected included primary data and secondary data. In this study the authors describe some of the indicators used are Procedure, Hours of Service, Cost Services, Product Services, Infrastructures and Services Provider Competency Officer. We then measured the Indicators variable, while the size of the variable in this study fall into three categories: Good, Pretty Good and Less Good. As a final conclusion in this research authors concluded that the Marriage Act Handling Services at the Office of Population and Civil Registration Pekanbaru city Categorized "Good Enough".